The Future of the Platform Society in Brazil (Intercom - Brazilian Journal of Communication Sciences, 2023)
The purpose of this article is to diagnose the platform society and propose actions that should be implemented over the next ten years in Brazil. An introduction to the theme of digital platforms is made, clarifying some fundamental concepts (data sovereignty and colonialism, datafication, infopower, and algorithmic governmentality). Then, the three central parts of the text are presented: a current diagnosis, perspectives on the future and some propositions of actions that must be thought and/or implemented to face the challenge of platforming society in Brazil.
Keywords: Platforms; Brazil; Future; Digital Culture; Power